Silvi-pastoral System for Development of Degraded Lands - Mishra, C. M.; Dubey, P.; Kumar, A. (Indian Forester, 2006)
Under the present investigation suitable silvipasture model has been developed for large scale planting of fodder tree-grass combination in saline-alkali soils of U.P. Three tree species viz. Leucaena leucocephala, Albizia lebbek and Cassia siamea along with forage grasses like Brachiaria mutica, Panicum maximum and Chloris gayana were planted in spacement of 4.0m Ã— 2.50m (Tree spp.) and 0.50m Ã— 0.50m (Grass spp.), respectively. The results revealed considerable improvement of the entire system with huge amount of fodder biomass production.